2012
DOI: 10.1111/j.1365-313x.2012.04908.x
|View full text |Cite
|
Sign up to set email alerts
|

Tandemly arranged chalcone synthase A genes contribute to the spatially regulated expression of siRNA and the natural bicolor floral phenotype in Petunia hybrida

Abstract: SUMMARYThe natural bicolor floral traits of the horticultural petunia (Petunia hybrida) cultivars Picotee and Star are caused by the spatial repression of the chalcone synthase A (CHS-A) gene, which encodes an anthocyanin biosynthetic enzyme. Here we show that Picotee and Star petunias carry the same short interfering RNA (siRNA)-producing locus, consisting of two intact CHS-A copies, PhCHS-A1 and PhCHS-A2, in a tandem headto-tail orientation. The precursor CHS mRNAs are transcribed from the two CHS-A copies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 42 publications
1
64
0
5
Order By: Relevance
“…Inhibition of enzyme activity involved in anthocyanin biosynthesis causes a decrease directly in anthocyanin concentration. In the white marginal tissue of a Petunia picotee ower, expression of chalcone synthase, an anthocyanin biosynthetic enzyme, was specifically repressed by endogenously operating post-transcriptional gene silencing (Saito et al 2006;Morita et al 2012). In addition to decreasing the anthocyanin concentration, a signi cant increase in the concentrations of caffeoyl glucosides and coumaroyl glucoside were found in white ower tissue compared with colored flower tissue (Saito et al 2006;Saito et al 2007).…”
Section: A Lighter Color Mutation Occurs From a Decrease In Anthocyanmentioning
confidence: 89%
“…Inhibition of enzyme activity involved in anthocyanin biosynthesis causes a decrease directly in anthocyanin concentration. In the white marginal tissue of a Petunia picotee ower, expression of chalcone synthase, an anthocyanin biosynthetic enzyme, was specifically repressed by endogenously operating post-transcriptional gene silencing (Saito et al 2006;Morita et al 2012). In addition to decreasing the anthocyanin concentration, a signi cant increase in the concentrations of caffeoyl glucosides and coumaroyl glucoside were found in white ower tissue compared with colored flower tissue (Saito et al 2006;Saito et al 2007).…”
Section: A Lighter Color Mutation Occurs From a Decrease In Anthocyanmentioning
confidence: 89%
“…The fertility of homozygous lines is reduced in comparison to wild-type plants (Table 1). Extensive gene redundancy in the CHS family in petunia (Koes et al 2005;Morita et al 2012) may be responsible for the lack of visible phenotype in the identified line. A novel mutant allele of the gene coding for the R2R3 MYB protein PH4 in whiteflowered plants was also identified (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2F). The color pattern-formation mechanisms have been studied in restricted species, such as Petunia (Hosokawa et al 2013, Koseki et al 2005, Morita et al 2012, Saito et al 2006, Saito et al 2007, van Houwelingen et al 1998, Dianthus (Itoh et al 2002, Momose et al 2013, Pharbitis (Iida et al 2004, Inagaki et al 1994, Camellia (Tateishi et al 2010), and Dahlia (Ohno et al 2011). In these species, the chemical structures and biosynthetic genes of anthocyanins have been well studied.…”
Section: Flower Pattern Typesmentioning
confidence: 99%
“…There are also exogenous factors such as viral infection and endogenous factors such as transposon and PTGS, which cause flower color pattern formation. The latter are probably the simplest research objects when studying differentiation mechanisms In this paper, I will present a general procedure to elucidate the mechanisms responsible for flower color pattern formation, referring to my own studies on the marginal picotee pattern of Petunia flowers to explain the idea in detail (Morita et al 2012, Saito et al 2006, Saito et al 2007. While pigments popularly distributed in plants are anthocyanins and carotenoids, those comprising flower color pattern are mainly anthocyanins or betalains.…”
Section: Fig 1 Flower Pattern Generated By Viral Infection In Tulipamentioning
confidence: 99%